Effects of motor control exercise and patient education program in the management of chronic low back pain among community-dwelling adults in rural Nigeria: a study protocol for a randomized clinical trial - Aminu A. Ibrahim; Mukadas O. Akindele; Sokunbi O. Ganiyu; Bashir Bello (Integrative Medicine Research)
Background: The impact of chronic low back pain (CLBP) is disproportionally higher in rural Nigeria than in urban areas but lack access to rehabilitation. While exercise and education are commonly advocated interventions for the rehabilitation of CLBP, there is a paucity of community-based randomized clinical trials assessing their benefits among adults with CLBP in rural Nigeria. The purpose of this study is to investigate the effects of motor control exercise (MCE) and patient education (PE) in the management of CLBP among community-dwelling adults in rural Nigeria. Methods: This is an assessor-blind, three-arm parallel randomized clinical trial and will be conducted at Tsakuwa Primary Health Care Center in Kano, Northwestern Nigeria. One hundred and twenty adults with CLBP will be recruited and randomized to one of three intervention arms; MCE plus PE, MCE, or PE groups. The MCE will be administered twice a week for 8 weeks while the PE will be provided once a week for 8 weeks. Participants will be assessed pre-intervention, immediately post-intervention and at 3-month post-intervention. Primary outcomes will be pain intensity and functional disability. Secondary outcomes will be quality of life, fear-avoidance beliefs, pain catastrophizing, back beliefs, global perceived recovery, and physical performance. Discussion: This will be the first community-based trial to assess the benefits of exercise and education in the management of CLBP among adults in rural Nigeria. The study may provide a relatively inexpensive, assessable, and effective alternative intervention for reducing CLBP disability in a low-resource rural Nigerian community. Trial registration: This study is registered at ClinicalTrial.gov and the trial registration number is NCT03393104. Keywords: Chronic low back pain, Community-dwelling adults, Motor control exercise, Patient education, Rural Nigeria